Changing diets and the role of rural food vendors in Cambodia - Ignowski, Elizabeth; Chitnavis, Shreya; Bun, Phanna; Chroeng, Chantha; Fiorella, Kathryn (WorldFish, 2024)
Cambodia, like many other low- and middle-income countries (LMICs), is undergoing a significant dietary shift. National data shows a decrease in the share of household expenditure on food over the past two decades, accompanied by an increase in purchased food items and food prepared away from home, indicative of a diet transformation. In this context, the rural economy relies heavily on informal food vendors and small-town market sellers, whose role is crucial yet often overlooked, particularly in rural areas. These vendors provide convenient access to a diverse range of affordable foods, including fresh produce, cooked meals, and ultra-processed snacks. However, this shift in consumption patterns, from home-cooked meals to food outside the home and readily available ultra-processed foods, poses nutritional challenges at both household and population levels, contributing to the phenomenon known as nutrition transition. CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD) has conducted and urban food vendor survey in Cambodia. This is a poster presentation on the study titled ''Changing diets and the role of rural food vendors in Cambodia''.